Whats next? : Malaysia web advertising for the future / Mohd Khairulnizam Ramli - Mohd Khairulnizam, Ramli (Universiti Teknologi MARA, Perak, 2017)
Marketing and advertising industry in Malaysia, especially those who are using digital media as a growing medium and use the various parties in Malaysia, as we can see and know the trend towards e-commerce website (buying, selling, marketing, advertising) increasingly in demand. Internet penetration (growing number of users), is the development of online digital media in Malaysia. All this has been proved by statistics that are made through studies and surveys on the development of the use of digital media as a medium by advertiser’s statistics taken from (internetworldstats.com, 2011).